Chetna's Indian feasts : everyday meals & easy entertaining - Makan, Chetna (Hamlyn, 2023)
Chetna Makan is the queen of Indian home cooking. First introduced to us on The Great British Bake Off, Chetna has since authored several bestselling cookbooks that combine her inventive flavors with a love of simple Indian recipes. In this newest collection, Chetna provides us with flavor-packed feasts designed to please a crowd. Chetna's accessible style and supermarket-friendly ingredients prove that you don't need to be an expert to entertain. Chetna's Indian Feasts provides a varied array of delicious dishes, grouped together by theme so you know exactly how to pair your platters. Whether this is a big celebration or a quick-fix family dinner, you will find enticing yet easy recipes for every occasion. Vibrant, varied and reliably delicious, Chetna's food will always impress.